Menyelamatkan Hutan melalui Instrumen Pembiayaan Berkelanjutan dan Penegakan Hukum terhadap Financial Backers - Ndaru, Felix Aglen (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
International reports show a correlation between financing and deforestation. Law enforcement has not fully touched financiers and beneficiaries. Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction is a progressive regulation that regulates the punishment of activities to fund forest destruction. Still, the offense is relatively rarely used by law enforcement. This study uses normative legal research methods and case studies. The study aims to dissect the concept of funding forest destruction and explore strategies for implementing sustainable financing. The study results show that the punishment for supporting forest destruction must be done by proving the element of guilt, namely the element of intentionality for individuals and at least culpa lata for corporations. To implement sustainable financing, strategies for financial institutions include strengthening the principal system of recognizing service users, active and continuous monitoring and auditing, and cross-sector collaboration. Financial institutions must also support policies and guidelines related to green financing, anti-money laundering, and anti-deforestation. The challenge of funding forest destruction is the existence of business actors who take refuge in complete permits and the absence of operational definitions in Law Number 18 of 2013. The case study results show that the punishment for funding forest destruction cannot be done partially but must simultaneously ensnare investors, forest destruction actors, and other parties who participate.